Fertigation system using IOT / Muhammad Khairullah Zainudin and Muhammad Imran Azhan - Zainudin, Muhammad Khairullah; Azhan, Muhammad Imran (2015)
This paper is about the concept of automatic automation of agronomy. The agricultural industry is very close compared to all other industries because the types of jobs involved in agriculture are unpredictable and many tedious tasks are not always the same. Many factors need to be taken into account (i.e. atmospheric conditions, soil status, etc.) before the work can be done. Prototype - "Fertility Systems Using IoT" is an autonomous agricultural tool to determine PPM levels using electrodes, minerals, types of fertilizers to be used and automatic fertilization to the plant. The type of crop to be grown is based on soil PPM value and can be determined from soil fertility test report. PPM values are determined using their respective Solid Solids (TDS sensors) and corrective actions for specific ranges are displayed. The corrective action shown occurs with the help of relay and valve setup. Therefore, with the help of Automatic Fertilization this setup is possible. The process is monitored using the IoT on the webpage.